EFFECT OF TURNING PARAMETERS ON METAL REMOVAL AND TOOL WEAR RATES OF AISI 1018 LOW CARBON STEEL (Nigerian Journal of Technology, 2016)
The quality of machined parts and tooling costs are major challenges encountered during the turning process. Therefore, optimum machining parameters suitable for turning operations must be selected in other to obtain the desired quality of the finished product at reduced machining time and cost. The present study was carried out on AISI 1018 low carbon steel during turning operation to reduce tooling costs as a result of tool wear and achieve optimum metal removal rate. Taguchi technique was employed using the L9 orthogonal array and the analysis of variance (ANOVA) to investigate the effect of the turning parameters on Metal Removal Rate (MRR) and Tool Wear Rate (TWR). The LARGER THE BETTER signal to noise (S/N) ratio based on the Taguchi technique was applied for MRR while the LOWER THE BETTER S/N ratio was applied for TWR. The results revealed that depth of cut is the most significant process parameter for MRR with a percentage contribution of the cutting speed and the feed rate are the most significant process parameters for TWR with percentage contributions of and respectively. The study concludes that AISI 1018 low carbon steel has a maximum MRR of and a minimum TWR of .  http://dx.doi.org/10.4314/njt.v35i4.20 Orthogonal array, Robust design, Tool wear rate, Metal removal rate